The Evaluation of Thin-Plate Low Carbon Steel in Spot Welding with Non-Destructive Test (NDT) and Destructive-Test (DT): Pressure Effect - Agus Sifa; T Endramawan; Badruzzaman Badruzzaman (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2021)
This paper has the purpose of how the pressure affects the weld quality and weldability on thin-plate low carbon steel with a thickness of 1 + 1 mm. The method used to know the impact of the welding quality by experimenting with the welding process with low carbon steel thin plate material with a composition of 99,65% Fe and 0,05% C, it is low carbon steel and has a thickness of 1 + 1 mm using Cu electrode by providing the various parameters given the pressure of 1-5 bar, testing of Non-Destructive Test (Ultrasonic Test) and Destructive Test (DT): shear testing, microstructure test. The result of NDT testing obtained deformation of thick plate thickness at 1 bar pressure has bigger deformation compared to 5 bar pressure, while in microstructure test result of 1-2 bar pressure has better weldability than the pressure of 3-5 bar, while the result of the tensile - shear test obtained a large load of 1 bar of 544 kgf greater than 5 bar tensile - shear test with load 248 kgf, it can be recommended for welding on thin-plate low carbon steel 1 + 1 mm thickness can be given 1 bar loading.